Jewelery Design: Playful Niobio Earrings for Girls 4 to 7 Years (Research, Society and Development, 2019)
The jewel carries in itself a great symbolic and aesthetic value, being chosen as present by parents who wish to convey this meaning, but the child has his own way of thinking and reacting to objects and often does not understand this value. The aimof this work is to develop a playful jewelry for girls from four to seven years, aiming for a more relevant interaction to that public. The Löbach design methodology and Baxter tools have been used to identify possible problems and demands related to that product. A questionnaire has been applied to collect data regarding the trend of the consumer public. It has been presented, as a final product, a pair of earrings so called Sorvetinho, the materials used in the pieces were gold and niobium, because they present hypoallergenic characteristics demanded in the project. The final product achieved satisfactory results, since it was possible to develop a safe part and met the necessary requirements of the project.